Retention of case-based learning on infectious diseases by third-year medical students - S., Kartikeyan; Malgaonkar, Aniruddha A. (International Journal of Research in Medical Sciences, 2016)
Background: Undergraduate medical students infrequently see a variety of cases of infectious diseases during their batch-wise rotatory clinical postings. Traditional didactic teaching resulted in lack of learner-centred teaching, lack of in-depth knowledge and less retention of learning. The main aim and objective of this complete-enumeration, before-and-after study (without controls) is to employ case-based learning (CBL) as an adjunct to traditional didactic lectures (TDL) for teaching infectious diseases to third-year undergraduate medical students to study the retention of knowledge by comparing the cognitive domain scores in pre- and post-tests. Methods: After obtaining ethical permissions and written informed consent, TDLs were delivered to give a preview on ten topics (selected by lottery system from topics in syllabus) and a pre-test was conducted after TDL. After pre-test, CBL sessions were conducted jointly by two facilitators (using identical CBL modules) in two randomly-assigned sub-groups (n=28) to enable discussion. After CBL, two post-tests (identical to pre-test) were conducted at intervals of one and six months to determine the levels of retention of learning. Results: The differences in the student-wise and question-wise scores in the pre-test and one-month post-test and that between the pre-test and six-month post-test were highly significant. However, the difference between the mean scores in one-month and six-month post-test were not statistically significant. Conclusions: CBL modules using case scenarios were found to enable learning. The marginal differences between the scores in the one-month and six-month post-tests indicate that a single post-test administered six months after the educational intervention (CBL) would be adequate.